Organizational image/reputation - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2017)
Organizational image refers to people’s global impressions of an organization and is defined as people’s loose structures of knowledge and beliefs about an organization. Organizational image represents the net cognitive reactions and associations of customers, investors, employees, and applicants to an organization’s name. Accordingly, it serves as a template to categorize, store, and recall organization-related information.